Developing an Executive Functioning Composite Score for Research and Clinical Trials. (21st January 2020) - Iverson, Grant L; Karr, Justin E; Terry, Douglas P; Garcia-Barrera, Mauricio A; Holdnack, James A; Ivins, Brian J; Silverberg, Noah D
Abstract: Objective: Executive functioning encompasses interactive cognitive processes such as planning, organization, set-shifting, inhibition, self-monitoring, working memory, and initiating and sustaining motor and mental activity. Researchers therefore typically assess executive functioning with multiple tests, each yielding multiple scores. A single composite score of executive functioning, which summarizes deficits across a battery of tests, would be useful in research and clinical trials. This study examines multiple candidate composite scores of executive functioning using tests from the Delis–Kaplan Executive Function System (D-KEFS). Method: Participants were 875 adults between the ages of 20 and 89 years from the D-KEFS standardization sample. Seven Total Achievement scores were used from three tests (i.e., Trail Making, Verbal Fluency, and Color–Word Interference) to form eight composite scores that were compared based on their psychometric properties and association with intelligence (IQ). Results: The distributions of most composite scores were mildly to severely skewed, and some had a pronounced ceiling effect. The composite scores all showed a medium positive correlation with IQ. The composite scores were highly intercorrelated in the total sample and in four IQ subgroups (i.e., IQ <89, 90–99, 100–109, 110+), with some being so highly correlated that they appear redundant. Conclusions: This study is part of a larger research program developing a cognition endpoint for research and clinical trials with sound psychometric properties and utility across discrepant test batteries. Future research is needed to examine the reliability and ecological validity of these composite scores.